Upholding the right work ethic and integrity while working from home / Nur Rasyida Mohd Rashid and Dr Sharfizie Mohd Sharip - Mohd Rashid, Nur Rasyida; Mohd Sharip, Sharfizie (UiTM Cawangan Negeri Sembilan, 2022)
Work from Home (WFH) is a term that all Malaysian workers are familiar with since the outbreak of the Covid-19 pandemic in 2020. As a result, the implementation of WFH has grown popular and has become a top priority for many private companies and civil services. Many claimed that measuring the effectiveness and efficiency of the workers' performance was quite challenging since the deployment of WFH. This is due to the lack of a specific method or tool for monitoring staff integrity while working at home. Furthermore, many employees perceive that it is difficult and challenging to stay focused on work due to family members' interference and poor internet connection. Those were the issues regarding the employee's working quality and performance queried by the employers.